Automating the semantic mapping between regulatory guidelines and organizational processes. Issue 4 (December 2016) - Sapkota, Krishna; Aldea, Arantza; Younas, Muhammad; Duce, David; Banares-Alcantara, Rene
Abstract The mapping of regulatory guidelines with organizational processes is an important aspect of a regulatory-compliance management system. Automating this mapping process can greatly improve the overall compliance process. Currently, there is research on mapping between different entities such as ontology mapping, sentence similarity, semantic similarity and regulation-requirement mapping. However, there has not been adequate research on the automation of the mapping process between regulatory guidelines and organizational processes. In this paper, we explain how Natural Language Processing and Semantic Web technologies can be applied in this area. In particular, we explain how we can take advantage of the structures of regulation-ontology and the process-ontology in order to compute the similarity between a regulatory guideline and a process. Our methodology is validated using a case study in the Pharmaceutical industry, which has shown promising results.